Science, Uncertainty, and Values in Ecological Restoration: A Case Study in Structured Decision‐Making and Adaptive Management. Issue 4 (28th September 2012) - Failing, Lee; Gregory, Robin; Higgins, Paul
Abstract This article demonstrates a structured and collaborative approach to decision‐making in the context of adaptive management experiments, using a case study involving the restoration of a hydrological regime in a regulated river in western Canada. It provides a framework based on principles of decision analysis for structuring difficult multi‐attribute decisions and building the trust and technical capacity needed to implement them. Participants included ecologists and fisheries biologists, government regulators, electric utility employees, and representatives of aboriginal communities. The case study demonstrates a values‐based approach to implementing adaptive management that addresses some of the long‐standing difficulties associated with integrating adaptive management into restoration decisions. It highlights practical methods for incorporating participants' values concerned with learning, cultural quality, and stewardship as part of developing a decision‐making and monitoring framework for restoration initiatives. It also provides an example of how to implement principles of meaningful consultation in a restoration context, with emphasis on ensuring that all voices and concerns are heard and meaningfully incorporated. Participants have adopted the framework as a model to guide future collaborative decision‐making processes involving Aboriginal communities, regulatory agencies, and other parties.